Effect of silica nanoparticles in mixed matrix membranes for pervaporation dehydration of acetic acid aqueous solution: plant-inspired dewatering systems. (20th January 2016) - Jullok, Nora; Van Hooghten, Rob; Luis, Patricia; Volodin, Alexander; Van Haesendonck, Chris; Vermant, Jan; Van der Bruggen, Bart
Abstract: Clean technology in dehydration of acetic acid using pervaporative separations inspired by plant dewatering systems is studied in this work. The novel polyphenylsulfone-based membranes, modified with silica nanoparticles, were used to dehydrate a binary mixture of acetic acid and water. The Stöber process was applied for the synthesis of monodispersed silica colloids by hydrolysis of alkyl silicates and condensation of silicic acid in alcoholic solution. The surface free energy of the synthesized silica particles was altered through a silanization treatment with hexamethyldisilazane to convert the surface hydroxyl groups to trimethylsilyl[–Si(CH3 )3 ] groups. The synthesized particles and the modified polyphenylsulfone based membranes were characterized using dynamic light scattering, scanning electron microscopy, atomic force microscopy, Fourier-transform infrared and macroscopic contact angle measurements. Pervaporation was used for the dehydration of 70 wt% acetic acid at 70 °C using nine different membrane variations. Inspired by the natural dewatering in plants containing silica, the performance of the synthetic silica nanoparticles filled-membranes was investigated. Similar to plants, the incorporation of silica nanoparticles in these membranes significantly affected the dewatering process. It was found that at higher concentrations of silica, an improvement of membrane properties was observed, particularly in terms of selectivity. Besides that, the hydrophilicity and surface roughness increases when sufficient amounts of silanols groups were present on the membrane surface. It was concluded that more hydrophilic silica should be first produced and incorporated into the membranes for efficient removal of water from acetic acid. This can be achieved by controlling the composition ratio of ammonium hydroxide, water and ethanol for the nanoparticle fabrication. The effect of different nanoparticle types on membrane morphology and pervaporation performance is also discussed in detail in this work. Highlights: Clean technology for dehydration of organic acid. Pervaporation, which inspired by the dewatering potential of plants containing silica. The Stöber process was applied for the synthesis of monodispersed silica. Silica in plants and membranes has a significant effect on the dehydration. Comparison of present membranes with literature data.